Inclusion and Exclusion of Social Actors in Judi Online ‘Online Gambling’ News:A Corpus-Assisted Critical Discourse Analysis Approach on Kompas.com - Budiawan, Raden Yusuf Sidiq; Mualafina, Rawinda Fitrotul; Siti Ulfiyani; Mukhlis (ETERNAL (English Teaching Journal), 2025)
Abstract. This study aims to describe the inclusion and exclusion of social actors in online gambling news coverage on Kompas.com using a critical discourse analysis approach assisted by corpora. By utilizing this approach, the language patterns used in the coverage are systematically analyzed to explore how the issue of online gambling is framed by the media. The findings reveal that the coverage predominantly features the government, such as "Budi Arie", in a positive role as an active actor in the fight against online gambling (inclusion). The government is portrayed as the key and dominant force in addressing this issue. In contrast, the online gambling perpetrators and victims are more frequently ignored or concealed (exclusion). The perpetrators are depicted as destructive agents responsible for the issue, while victims are often portrayed as suffering individuals who require external intervention. The language use that emphasizes the government's role highlights efforts to reinforce their legitimacy in addressing this social problem. Thus, the analysis shows that Kompas.com's news coverage tends to present a discourse that supports the government's role in tackling online gambling, while minimizing the representation of perpetrators and victims.